Prevalence of Helicobacter pylori infection among Slovenian children and adolescents: A prospective cohort study - Šterbenc, Anja; Godnov, Uroš; Vodičar, Polona Maver; Simčič, Saša; Jeverica, Samo; Zaletel, Živa; Homan, Pia; Mojškerc, Eva Miler; Homan, Matjaž (Helicobacter (Cambridge, Mass.), 2024)
Background Helicobacter pylori (H. pylori) infection is primarily acquired in childhood and is notably influenced by socioeconomic variances across different geographical regions. The aim of this study is to assess the prevalence of H. pylori infection in Slovenian children and to identify potential risk factors that facilitate the infection. Materials and Methods Between 2019 and 2022, we conducted a multi‐center prospective cross‐sectional study among healthy children residing in three different administrative regions in Slovenia. H. pylori infection status was determined using a monoclonal antibody‐based stool antigen test (SAT). A standardized questionnaire was designed to evaluate the influence of various H. pylori‐associated risk factors, including demographics and socioeconomic, housing and sanitation conditions. Results During the 3‐year period, we recruited a total of 421 children and adolescents (age range 2–18 years, mean age 10.29 ± 4.95 years). Overall, 46 (10.9%) were diagnosed with H. pylori infection. No associations were found between H. pylori prevalence rates and increasing age, sex, parental education level, country of birth of the child or their parents, number of household members, household income, having a dishwasher, owning a pet, duration of breastfeeding, fruit intake frequency, drinking tap water, and handwashing practices. The only parameters associated with an increased risk of infection were the location of the school (p < 0.001) and living in an urban area (p = 0.036). The odds of infection were approximately 4.77 times higher if the child attended school in the Central Slovenian compared to other regions (OR = 4.77; 95% CI 0.87–2.34). Conclusions This is the first study providing information on the prevalence of H. pylori infection among Slovenian children and adolescents. Using SAT, we have shown that the burden of H. pylori infection in our pediatric population is low; however, it seems to depend on regional rather than socioeconomic factors.